1996
DOI: 10.1063/1.361520
|View full text |Cite
|
Sign up to set email alerts
|

Distinction between electron and hole traps in semi-insulating GaAs

Abstract: Traps are commonly characterized in semi-insulating materials using a thermally stimulated current technique that cannot discriminate between electron and hole traps. We describe a combination of several thermally stimulated techniques that allow us to distinguish electron traps from hole traps. It is applied to semi-insulating GaAs where the EL2 defects present in this material introduce holes in the valence band when they are transformed into their metastable states. The nature, donor or acceptor, of the tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
3
0

Year Published

1997
1997
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…Fig.4 shows the TSC and TSHV spectra taken after 100sec exposure(during PQ) with of 1.16eV light. By comparing the TSHV and TSC spectra, we observe, (i) the metastable TSC peaks at 26K and 140K are present in TSHV spectra and hence these are hole traps [13], (ii) the TSC peaks at 65K, 90K and 120K are absent, instead a dip at their positions and these should be due to electron traps [13], which should give rise to negative peak in TSHV spectra.…”
mentioning
confidence: 92%
“…Fig.4 shows the TSC and TSHV spectra taken after 100sec exposure(during PQ) with of 1.16eV light. By comparing the TSHV and TSC spectra, we observe, (i) the metastable TSC peaks at 26K and 140K are present in TSHV spectra and hence these are hole traps [13], (ii) the TSC peaks at 65K, 90K and 120K are absent, instead a dip at their positions and these should be due to electron traps [13], which should give rise to negative peak in TSHV spectra.…”
mentioning
confidence: 92%
“…residual donors (usually Si) and shallow carbon acceptors which are intentionally introduced in GaAs at the level of n C $ 0:5 Â 10 15 cm À3 . However, thermally stimulated (TS) current in conjunction with TS Hall effect measurements [14] have demonstrated that the concentration of the deep hole traps in SI-GaAs is of the same order as the concentration of the deep electron traps, and that the pinning of the Fermi level on the EL2 midgap may be explained as a result of the balance between deep electron and hole traps. The capture of electrons by the EL2 þ traps occurs over a configuration barrier with energy of $0:066 eV [15].…”
mentioning
confidence: 99%
“…However, the Fermi level (EF) is often found to lie below the EL2 midgap level, implying the existence of deep acceptor defects which can act like hole traps. Thermally stimulated (TS) current in conjunction with TS Hall effect measurements [14] have demonstrated that the concentration of the deep hole traps in SI-GaAs is of the same order as the concentration of the deep electron traps, and that the pinning of the Fermi level on the EL2 midgap may be explained as a result of the balance between deep electron and hole traps. The capture of electrons by the EL2 + traps occurs over a configuration barrier with energy of ∼ 0.066 eV [15].…”
mentioning
confidence: 99%